2014
DOI: 10.3390/ma7074930
|View full text |Cite
|
Sign up to set email alerts
|

Welding and Joining of Titanium Aluminides

Abstract: Welding and joining of titanium aluminides is the key to making them more attractive in industrial fields. The purpose of this review is to provide a comprehensive overview of recent progress in welding and joining of titanium aluminides, as well as to introduce current research and application. The possible methods available for titanium aluminides involve brazing, diffusion bonding, fusion welding, friction welding and reactive joining. Of the numerous methods, solid-state diffusion bonding and vacuum brazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 129 publications
(295 reference statements)
1
14
0
1
Order By: Relevance
“…The tensile results were consistent with the microstructural distribution of the welded joints, and it suggested that the post-weld heat treatment (PWHT) can improve the mechanical properties in brittle Ti alloy welds [18]. Additionally, it was reported that when welding Ti-Al alloys as the one used in this investigation, careful control of the welding parameters is necessary to obtain a sound joint [39,40]. When the tensile tests were performed at 650 • C, the yield strength and tensile strength drastically decreases to approximately 679 MPa and 765 MPa (about 82% and 86% of that of the base material at the same testing temperature), respectively.…”
Section: Mechanical Properties Of the Jointssupporting
confidence: 65%
“…The tensile results were consistent with the microstructural distribution of the welded joints, and it suggested that the post-weld heat treatment (PWHT) can improve the mechanical properties in brittle Ti alloy welds [18]. Additionally, it was reported that when welding Ti-Al alloys as the one used in this investigation, careful control of the welding parameters is necessary to obtain a sound joint [39,40]. When the tensile tests were performed at 650 • C, the yield strength and tensile strength drastically decreases to approximately 679 MPa and 765 MPa (about 82% and 86% of that of the base material at the same testing temperature), respectively.…”
Section: Mechanical Properties Of the Jointssupporting
confidence: 65%
“…The development of joining technologies has become an essential requirement for application of these alloys in replacing traditional metallic alloys in aerospace and automotive applications [3][4][5][6]. However, there are only a few reports regarding the techniques used to join TiAl alloys with other materials [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional titanium alloys are continuously challenged by the operation at temperatures higher than 550 • C due to poor high temperature oxidation resistance and creep properties [2]. Whence, the investigations on the production, characterization, and joining of titanium alloys as titanium aluminides (TiAl), TiNi and Ti6Al4V, have increased during the last decades [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Dissimilar joints between titanium alloys are essential for their successful integration into high temperature aerospace and automobile applications combining unique properties as well as overcoming some disadvantages of these alloys [5]. For instance, the joining of TiNi and Ti6Al4V alloys is vital for the development of a shape memory alloy (SMA) adaptive serrated nozzle to aid noise reduction in next-generation gas turbine engines and the blade SMA actuator to enable in-flight rotor tracking in commercial and military helicopters [7,8].…”
Section: Introductionmentioning
confidence: 99%